If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -17 = 87x + 11 Reorder the terms: -17 + 7x = 87x + 11 Reorder the terms: -17 + 7x = 11 + 87x Solving -17 + 7x = 11 + 87x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-87x' to each side of the equation. -17 + 7x + -87x = 11 + 87x + -87x Combine like terms: 7x + -87x = -80x -17 + -80x = 11 + 87x + -87x Combine like terms: 87x + -87x = 0 -17 + -80x = 11 + 0 -17 + -80x = 11 Add '17' to each side of the equation. -17 + 17 + -80x = 11 + 17 Combine like terms: -17 + 17 = 0 0 + -80x = 11 + 17 -80x = 11 + 17 Combine like terms: 11 + 17 = 28 -80x = 28 Divide each side by '-80'. x = -0.35 Simplifying x = -0.35
| 5n-5=4 | | 7(g-4)=3+7g | | 6.4a+7.85=2.6a+9.69 | | log(4x-3)=4 | | 12+18=17+7q | | K/2-3=4 | | -2000000-800000x=1600000 | | 5n+2=2(n+2)+3n | | x/x-10=10/2 | | Q=RYG | | 4a+10=13 | | 10v+4(10+5v)= | | x-2=25-6 | | -24=n-25 | | 7/9=10/x-7 | | 4ln(x)+3y=1 | | (x-4)-3=0 | | y=(0.0025s^2+0.05s+1)(s^2+0.8s+30)-28.6 | | 1/5-1=2/3 | | 1/5c=105 | | -8-11q=-2q+10 | | (8x^2+6x-5)-(10x^2-9x+5)= | | -5(1-8v)=-5(1+3v) | | ((3x^2-1))/(4x(x-5))÷((3x^2-1)(x-1))/((x-5)) | | -9-15=12 | | 15m^2-23m=0 | | 162+17m=281 | | 6=0.03x-1.2 | | 24n-36=396 | | 2(-1)+5z=-2 | | 15*(7-7)+(5*2)=x | | -16+0.6x=8 |